EKSISTENSI PEREMPUAN DALAM MENINGKATKAN PENDAPATAN PADA KELUARGA MISKIN KECAMATAN NEGARA KABUPATEN JEMBRANA - Krismayanti, Luh Venny; Budhi, Made Kembar Sri (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2022)
The role of women that is highlighted in development is that there are three roles of women as HR (Human Resources) in development, women as family builder, and women as development actors. The purpose of this study was to analyze the direct and indirect effects of the variables of education level, work experience and number of family dependents on the outpouring of working hours for women in poor families in the State District of Jembrana Regency. The data used are primary and secondary data. Samples as many as 81 respondents with path analysis techniques (path analysis). Based on the results of the study, it was shown that the level of education, work experience and number of family dependents had a positive effect on the outpouring of working hours for women in poor families. Education level, work experience, number of dependents and working hours have a positive effect on the contribution of women's income to poor families. Education level, work experience, number of family dependents through the outpouring of working hours indirectly have no effect on the income contribution of women to poor families in the State District of Jembrana Regency.   Keywords: women, poor families, work experience, education, family dependents, income